Answer:
![4\left(2x+7\right)-3\left(x+5\right)=5x+13](https://tex.z-dn.net/?f=4%5Cleft%282x%2B7%5Cright%29-3%5Cleft%28x%2B5%5Cright%29%3D5x%2B13)
Step-by-step explanation:
Given the expression
![4\left(2x+7\right)-3\left(x+5\right)](https://tex.z-dn.net/?f=4%5Cleft%282x%2B7%5Cright%29-3%5Cleft%28x%2B5%5Cright%29)
<u>Expand and simplify the expression</u>
![4\left(2x+7\right)-3\left(x+5\right)](https://tex.z-dn.net/?f=4%5Cleft%282x%2B7%5Cright%29-3%5Cleft%28x%2B5%5Cright%29)
Expand 4(2x + 7) = 8x + 28
![4\left(2x+7\right)-3\left(x+5\right)=8x+28-3\left(x+5\right)](https://tex.z-dn.net/?f=4%5Cleft%282x%2B7%5Cright%29-3%5Cleft%28x%2B5%5Cright%29%3D8x%2B28-3%5Cleft%28x%2B5%5Cright%29)
Expand -3(x + 5) = -3x - 15
![=8x+28-3x-15](https://tex.z-dn.net/?f=%3D8x%2B28-3x-15)
Group like terms
![=8x-3x+28-15](https://tex.z-dn.net/?f=%3D8x-3x%2B28-15)
Add similar elements: 8x - 3x = 5x
![=5x+28-15](https://tex.z-dn.net/?f=%3D5x%2B28-15)
Simplify
![=5x+13](https://tex.z-dn.net/?f=%3D5x%2B13)
Therefore, we conclude that:
![4\left(2x+7\right)-3\left(x+5\right)=5x+13](https://tex.z-dn.net/?f=4%5Cleft%282x%2B7%5Cright%29-3%5Cleft%28x%2B5%5Cright%29%3D5x%2B13)
19.2 * 10⁸ minutes.
60 minutes = 1 hour.
19.2 * 10⁸ minutes = (19.2 * 10⁸) / 60 hour
= 32 000 000 = 3.2 * 10⁷ hours
= <span>D. 3.200 × 10^7 h</span>
The answer is 30,60,90. Because 60 is twice the number 30 and 90 is three times the first number.
Answer:
![x \: = \: \boxed{ \bold{ - 4 }}\: \: \text{or} \: \: x \: = \: \boxed{ \bold{ 8}}](https://tex.z-dn.net/?f=x%20%20%5C%3A%20%3D%20%5C%3A%20%20%5Cboxed%7B%20%5Cbold%7B%20%20-%204%20%20%7D%7D%5C%3A%20%20%20%20%5C%3A%20%20%20%20%5Ctext%7Bor%7D%20%5C%3A%20%20%20%5C%3A%20x%20%5C%3A%20%20%3D%20%5C%3A%20%20%5Cboxed%7B%20%5Cbold%7B%208%7D%7D)
Step-by-step explanation:
![(x \: - \: 2 {)}^{2} \: + \: 2 \: = \: 38](https://tex.z-dn.net/?f=%28x%20%5C%3A%20%20-%20%20%5C%3A%202%20%7B%29%7D%5E%7B2%7D%20%20%5C%3A%20%20%2B%20%20%5C%3A%202%20%5C%3A%20%20%3D%20%20%5C%3A%2038)
![{x}^{2} \: - \: 4x \: + \: 4 \: + \: 2 \: = \: 38](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%5C%3A%20%20-%20%20%5C%3A%204x%20%5C%3A%20%20%2B%20%20%5C%3A%204%20%5C%3A%20%20%2B%20%20%5C%3A%202%20%5C%3A%20%20%3D%20%20%5C%3A%2038)
![{x}^{2} \: - \: 4x \: + \: 6 \: = \: 38](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%5C%3A%20%20-%20%20%5C%3A%204x%20%5C%3A%20%20%2B%20%20%5C%3A%206%20%5C%3A%20%20%3D%20%20%5C%3A%2038)
![{x}^{2} \: - \: 4x \: + \: 6 \: - \: 38 \: = \: 0](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%5C%3A%20%20-%20%20%5C%3A%204x%20%5C%3A%20%20%2B%20%20%5C%3A%206%20%5C%3A%20%20-%20%20%5C%3A%2038%20%5C%3A%20%20%3D%20%20%5C%3A%200)
![{x}^{2} \: + \: 4x \: - \: 8x \: - \: 32 \: = \: 0](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%5C%3A%20%20%2B%20%20%5C%3A%204x%20%5C%3A%20%20-%20%20%5C%3A%208x%20%5C%3A%20%20-%20%20%5C%3A%2032%20%5C%3A%20%20%3D%20%20%5C%3A%200)
![x \: \times \: (x \: + \: 4) \: - \: 8(x \: + \: 4) \: = \: 0](https://tex.z-dn.net/?f=x%20%5C%3A%20%20%5Ctimes%20%20%5C%3A%20%28x%20%5C%3A%20%20%2B%20%20%5C%3A%204%29%20%5C%3A%20%20-%20%20%5C%3A%208%28x%20%5C%3A%20%20%2B%20%20%5C%3A%204%29%20%5C%3A%20%20%3D%20%20%5C%3A%200)
![(x \: + \: 4) \: \times \: (x \: - \: 8) \: = \: 0](https://tex.z-dn.net/?f=%28x%20%5C%3A%20%20%2B%20%20%5C%3A%204%29%20%5C%3A%20%20%20%5Ctimes%20%20%5C%3A%20%28x%20%5C%3A%20%20-%20%20%5C%3A%208%29%20%5C%3A%20%20%3D%20%20%5C%3A%200)
- When it happens that the product of the factors is the same as zero. It is divided into two possible cases.
![x \: + \: 4 \: = \: 0 \\ x \: - \: 8 \: = \: 0](https://tex.z-dn.net/?f=x%20%5C%3A%20%20%2B%20%20%5C%3A%204%20%5C%3A%20%20%3D%20%20%5C%3A%200%20%5C%5C%20x%20%5C%3A%20%20-%20%20%5C%3A%208%20%5C%3A%20%20%3D%20%20%5C%3A%200)
- We solve the two equations:
![x \: = \: - 4 \\ x \: = \: 8](https://tex.z-dn.net/?f=x%20%5C%3A%20%20%3D%20%20%5C%3A%20%20-%204%20%5C%5C%20x%20%5C%3A%20%20%3D%20%20%5C%3A%208)
<h2>Answer: </h2>
![x \: = \: - 4 \\ x \: = \: 8](https://tex.z-dn.net/?f=x%20%5C%3A%20%20%3D%20%20%5C%3A%20%20-%204%20%5C%5C%20x%20%5C%3A%20%20%3D%20%20%5C%3A%208)
<h3><em><u>MissSpanish</u></em></h3>
Answer:
54.6
Step-by-step explanation:
42 = 70%
100% - 70% = .30%
42 x 1.3 = 54.6